2017
DOI: 10.1108/jhom-04-2017-0074
|View full text |Cite
|
Sign up to set email alerts
|

Work motivation among healthcare professionals

Abstract: Purpose The purpose of this paper is to explore work motivation among professionals at well-functioning primary healthcare centers subject to a national healthcare reform which include financial incentives. Design/methodology/approach Five primary healthcare centers in Sweden were purposively selected for being well-operated and representing public/private and small/large units. In total, 43 interviews were completed with different medical professions and qualitative deductive content analysis was conducted. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 39 publications
1
30
0
1
Order By: Relevance
“…Similar to this review, a study in India reported that regular training was reported as a motivating factor in India [ 53 ]. In Sweden, a study reported provision of remuneration as an important element of motivation, suggesting that monetary incentives be coupled with the quality of healthcare service delivery to patients [ 55 ]. These findings show that health policymakers and managers should aim at creating both monetary and non-monetary motivational packages for the health workforce [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to this review, a study in India reported that regular training was reported as a motivating factor in India [ 53 ]. In Sweden, a study reported provision of remuneration as an important element of motivation, suggesting that monetary incentives be coupled with the quality of healthcare service delivery to patients [ 55 ]. These findings show that health policymakers and managers should aim at creating both monetary and non-monetary motivational packages for the health workforce [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare workers are motivated by transformative leaders who exhibit qualities such as idealised influence-behaviour, intellectual stimulation and inspirational motivation, not transactional or laissez-faire leaders [ 31 ]. Similarly, a study in Sweden emphasised the role of positive management, including provision of clear direction, non-hierarchical collaboration, clear communication and systematic empowerment geared towards motivating the healthcare workers [ 55 ]. In 2015, a study in Iran reported good and support manager and supervisors and having good working relations with co-workers being motivators of healthcare workers [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Change in practice is influenced in many more ways than politics. First, we suggest that the long tradition, support and familiarity of improvement work in Jönköping County Council provided fertile ground for innovation [27, 38]. Second, we believe that the mix of professionals in Swedish primary health care has great potential for the emergence of new practices.…”
Section: Discussionmentioning
confidence: 99%
“…The professional role of managers at PCUs varies. Six well-functioning PCUs from one county in Sweden were carefully chosen to be included in this study [18]. The purposive sampling focused on well-functioning PCUs, defined as PCUs providing high-quality care according to national and regional comparisons (e.g.…”
Section: Study Population and Methodsmentioning
confidence: 99%